Model‐free power control for low‐voltage ac dispatchable microgrids with multiple points of connection† - Dos Reis, Geovane; Liberado, Eduardo [UNESP]; Marafão, Fernando [UNESP]; Sousa, Clodualdo; Silva, Waner; Brandao, Danilo (MDPI, 2021)
This paper proposes a modified version of the power‐based control (MPBC) applied to microgrids (μGs) with multiple points of connection (i.e., utility grid itself or any other neighboring μG). Using the MPBC, single‐phase distributed energy resources (DERs) arbitrarily connected between the phases share the amounts of balanced power, while the unbalanced and homopolar power are steered only to the line‐to‐neutral inverters. The control technique is based on a three-level hierarchical control using narrow bandwidth, low data rate communication that properly coordinates the DERs connected to three‐phase four‐wire μGs. The MPBC allows the DERs to steer power flow at any of the multiple points of common coupling of a multi‐PCC dispatchable μG. The modified control proposed herein is evaluated through simulation results using MATLAB/SIMULINK considering a real urban distribution grid with typical operational elements and conditions. When compared to the original power‐based control (PBC), results show that a meshed μG may reach power benchmarks with accommodation time 80% lower when applying MPBC. Moreover, it may also lead to significant power loss reduction (about of 5%) in some studied cases.
Keywords: Dispatchable microgrids; Hierarchical control; Multi‐PCC microgrids; Power sharing